SUPERVISION OF SHARIA COOPERATIVES BASED ON FINANCIAL STATEMENTS: Analysis of Financial Statements of BMT Tumang 2015-2019 - Dwi Harmoyo; M. Arif Kurniawan (NUsantara Islamic Economic Journal, 2022)
This research discusses the supervision of sharia cooperative with financial statement basic, the document study of BMT Tumang Financial Statement from 2015 to 2019 Year. The research is sequential exploratory research, it's mean to mix between quantitative research and qualitative research, quantitative method to use financial statement analyze approach next to explained in qualitative descriptive approach. The purposes of the research to assess and describe into criteria (disobedient, less obedient, quite obedient, obedient) of cooperative compliance, financial compliance, and sharia compliance. Cooperative compliance that consists of cooperative principles such as: giving, democratist, justice of profit laverge, resource appreciate, and independence. Financial compliance that consists of financial management such as: capitaly, productive assets, efficiency, liquidity, and growth. Sharia compliance that consists of sharia principle such as: amanah, muamalah, khalifah, 'is, interest free, and uncentralistic economic. The result of the research show that BMT Tumang has obedient to compliance of membering, abedient to compliance of democratic, less obedient to compliance of justice, less obedient to compliance of profit laverge, quite obedient to compliance of resource appreciate, and less obedient to compliance of independence. BMT Tumang has less obedient to compliance of capitaly, obedient to compliance of productive assets, quite obedient to compliance of efficiency, less obedient to compliance of liquidity, less obedient to compliance of growth. BMT Tumang has obedient to compliance of amanah, quite obedient to compliance of muamalah, obedient to compliance of khalifah, less obedient to compliance of 'is, less obedient to compliance of interest free and obedient to compliance of uncentralistic economic. The research results would be better use observation and interview also. The supervision of sharia cooperative with financial statement basic aspected is useful for supervisors of sharia cooperative to compliance assessment.